Pengaruh Berat Karbon Aktif Kulit Jagung terhadap Penurunan COD (Chemical Oxygen Demand) Limbah Cair Industri Batik - Mifbakhuddin Mifbakhuddin; Fika Ardiani; Rahayu Astuti (Jurnal Kesehatan Masyarakat Indonesia, 2021)
Background: The batik industry produces chemical waste with a COD value of 1918 mg/l; (above the safe threshold of 150 mg/l). One of the wastewater treatment methods is using activated carbon, including corn husks. This study aims to determine the effect of the weight of corn husk activated carbon on the reduction of COD in batik industrial wastewater. Methods: A quasi-experimental study with a non-randomized pretest-posttest control group design using liquid waste from one of the batik industries in Rejomulyo Village, East Semarang District. This experiment applied five weight variations of corn husk activated carbon, namely 10, 20, 30, 40 and 50 grams with 4 repetitions, and 4 control samples. The effect of the treatment was observed in 50 minutes. The observations were analyzed using the Kruskal-Wallis statistical test. Results: The range and mean COD values before and after treatment were 3174.32 -5136.43 mg/l, and 584.29 - 1049.20 mg/l, respectively. The decrease in COD according to treatment ranged from 80.83% to 84.76%, while in the control group it was only 2.90%. There was an effect of the weight of corn husk activated carbon to decrease COD of batik industrial wastewater (p = 0.015), and there was an effect of the weight of corn husk activated carbon to decrease COD of batik industrial wastewater between control group and treatment group (p = 0.021). Conclusion: Corn husk activated carbon has a high potential to reduce the COD of chemical waste in the batik industry.